2004
DOI: 10.1042/cs20030326
|View full text |Cite
|
Sign up to set email alerts
|

Increase in long-chain polyunsaturated fatty acid n−6/n−3 ratio in relation to hepatic steatosis in patients with non-alcoholic fatty liver disease

Abstract: Hepatic steatosis is a major feature associated with NAFLD (non-alcoholic fatty liver disease). The aims of the present study were to assess the levels of PUFA (polyunsaturated fatty acids) in liver total lipids, triacylglycerols (triglycerides) and phospholipids of NAFLD patients in relation to those in adipose tissue and hepatic indexes related to oxidative stress as factors contributing to hepatic steatosis. Eleven control subjects and 19 patients with NAFLD were studied. Analysis of liver and abdominal adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
515
7
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(580 citation statements)
references
References 48 publications
(56 reference statements)
40
515
7
18
Order By: Relevance
“…The present study used FFAs to establish a cell model of human NAFLD. The results showed triglyceride accumulation in HepG2 cells after treatment with FFAs, consistent with previous studies [27][28][29][30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study used FFAs to establish a cell model of human NAFLD. The results showed triglyceride accumulation in HepG2 cells after treatment with FFAs, consistent with previous studies [27][28][29][30].…”
Section: Discussionsupporting
confidence: 81%
“…When obesity causes triglycerides failure to be stored in the adipose tissue, triglycerides are transformed into FFAs that are transported to nonadipose tissues [26]. Saturated palmitic (PA; C16:0) and monounsaturated oleic (OA; C18:1) acids are the most abundant FFAs in the liver triglycerides of patients with NAFLD [27,28]. Previous studies showed that in vitro NAFLD models induced by FFAs mixture (PA/OA, 1:2 ratio) could lead to triglyceride accumulation in hepatocytes similar to that of patients with NAFLD, with minor toxic and apoptotic effects [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This is associated with changes in gene expression, with decreased fatty acid oxidation and triacylglycerol export, and enhanced lipid synthesis, leading to fat accumulation in the liver. 19,27 We believe that macrosteatosis (as a feature of non-alcoholic fatty liver disease) results, at least partially, from abnormal hepatic lipid metabolism caused by imbalanced dietary PUFAs. Inadequate dietary intake of ␣-linolenic compared with lenoleic acid (the parent n-3 and n-6 PUFAs, respectively) leads to defective elongation and desaturation of ␣-linolenic acid because both compete for the enzymes responsible for their elongation and desaturation, leading to decreased production of ␣-linolenic acid long-chain derivatives (EPA and docosapentaenoic acid).…”
Section: Discussionmentioning
confidence: 99%
“…The current study was designed to assess the possible protective role of taurine against hypercholesterolemia-induced hepatic and cardic changes by histological and immunohistochemical studies. Ingestion of high-fat diet may lead to fatty acid accumulation and hepatic cell damage and inflammation (Araya et al, 2004). High fat diet have effects on cell death and steatosis (Mei et al, 2011).…”
Section: Discussionmentioning
confidence: 99%